Клінічна оцінка різних протоколів лікування собак за випадкових ран - Гергель, А. С.; Gergel, A. S.; Білий, Дмитро Дмитрович; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; et al. (Дніпровський ДАЕУ, 2022)
Визначено особливості перебігу, головні прогностичні маркери оцінки загоєння випадкових ран на тлі застосування різних схем лікування. Peculiarities of the course, the main prognostic markers for assessing the healing of accidental wounds on the background of the use of different treatment regimens are determined.
Clinical evaluation of various treatment protocols for dogs with accidental wounds
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384
Keywords: лікування; treatment; собаки; dogs; травми; injuries; рани; wounds